Int Adv Otol 2022
DOI: 10.5152/iao.2022.21541
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation for Patients with a Vestibular Schwannoma: Effect on Tinnitus Handicap

Abstract: Background: Tinnitus is a common symptom among individuals with a vestibular schwannoma. In recent years, cochlear implantation, often combined with tumor resection, is an increasingly used option in the management of these patients. The existing literature does not account well for the effect of treatment on tinnitus burden. Thus, this paper reports the effect of cochlear implantation on tinnitus in a cohort of vestibular schwannoma patients. Methods: Individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Cochlear implantation is a relatively new indication for hearing restoration in some VS patients and is relevant when the cochlear nerve is preserved during microsurgical tumor resection, following stereotactic radiation surgery, or when tumor resection is not attempted due to the tumor’s small size and the patient’s overall medical condition [ 84 ]. A retrospective cohort study of VS patients with tinnitus reported that median Tinnitus Handicap Inventory scores significantly improved after CI implantation (n = 17) [ 80 ], which is consistent with several prior small cohort studies that also reported improvements in tinnitus symptoms with CIs [ 85 , 86 , 87 ]. However, VS tumor management and the tumors themselves may have unpredictable effects on CIs’ function given the damage to the vestibulocochlear nerve.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Cochlear implantation is a relatively new indication for hearing restoration in some VS patients and is relevant when the cochlear nerve is preserved during microsurgical tumor resection, following stereotactic radiation surgery, or when tumor resection is not attempted due to the tumor’s small size and the patient’s overall medical condition [ 84 ]. A retrospective cohort study of VS patients with tinnitus reported that median Tinnitus Handicap Inventory scores significantly improved after CI implantation (n = 17) [ 80 ], which is consistent with several prior small cohort studies that also reported improvements in tinnitus symptoms with CIs [ 85 , 86 , 87 ]. However, VS tumor management and the tumors themselves may have unpredictable effects on CIs’ function given the damage to the vestibulocochlear nerve.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the limited available treatments, such as sound masking, hearing aids, or management of distressing symptoms with behavioral therapy, are associated with heterogenous efficacy and patient response. Several novel therapies, including the use of cochlear implants (CIs) and repetitive transcranial magnetic stimulation, have shown promise for tinnitus, although they remain experimental and are not routinely used in clinical practice [ 80 , 81 ]. CIs, which are typically reserved for patients with severe to profound sensorineural hearing loss, can alleviate tinnitus in 54–86% of patients without VS [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CI has been recommended as an auditory rehabilitation method for hearing loss associated with sporadic or NF2-related VS, whether resulting from the disease itself or the treatment used. 300 , 301 , 302 , 303 , 304 Initially, the CI was only indicated in patients with bilateral hearing loss, but is currently indicated for unilateral hearing loss as well, especially in patients with tinnitus, 127 , 305 , 306 with the goal of reestablishing the benefits of binaural hearing, such as enhanced spatial location and noise discrimination. 300 There are no standard criteria between different services for the indication of surgery, hearing evaluation, or preoperative prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, preservation of serviceable hearing should take precedence over solving tinnitus. With the development of medical technology, the preservation of the cochlear nerve provides a prerequisite for postoperative hearing reconstruction, and cochlear implantation will also have a positive impact on tinnitus [ 21 ]. Based on the above studies, we recommend that hearing preservation should be the principal objective for patients with serviceable preoperative hearing regardless of tumor size.…”
Section: Discussionmentioning
confidence: 99%